Abuse of power - Rosenberg, Nancy Taylor (Orion, 1997)
Courtroom drama in which police officer Rachel Simons' witness to a young boy's shooting by a fellow cop leads to a dangerous and lone quest for justice. By the author of California angel and Trial by fire.